The Place of British Electronic Dance Music - Sanders, Thomas (2022)
This dissertation explores the relations between contemporary electronic dance music (EDM) and the notion of place. Through a focus on three post-rave genres, I offer a spatial consideration of EDM itself and some of the different contexts in which it is performed and consumed. There are a range of complex and evolving geographies associated with dubstep, jungle and drum & bass music, all of which are styles of EDM seen to have a relationship with Britain. I work from interviews with artists, fans and industry professionals, a remote form of participant observation I refer to as ‘livestream fieldwork’, and my own experience as a participant in a range of EDM scenes. I first examine EDM’s ability to evoke a sense of place in its sound, despite a frequent lack of lyrical content and its almost entirely digital instrumentation. I draw on conceptualisations of the lineage of genres that stemmed from the rave scene to discuss the possible existence of a sound with a national quality in EDM, as recognised by my participants. Through a focus on livestreams, I then outline how the COVID-19 pandemic reshaped networks of creativity, reproduction, distribution and consumption within EDM by considering some of the sites that witnessed musical practice during ‘lockdown’ and the motivations behind mediated performances, ultimately theorising the internet as an important place for music at a time of crisis for the arts. However, the experiential difference between mediated and classic liveness was identified as profound, leading me to argue for the importance of physical space and copresence within live music. My conclusions indicate that place matters to people who engage with EDM in a variety of real and imagined ways, that are often unique to an individual.